FIXME: notation precedence not correct w.r.t. \to \land ...
- added notation for NLE
- added a comment to dependenciesParser.ml :p
[ ("->", <:unicode<to>>); ("=>", <:unicode<Rightarrow>>);
("<=", <:unicode<leq>>); (">=", <:unicode<geq>>);
("<>", <:unicode<neq>>); (":=", <:unicode<def>>);
+ ("==", <:unicode<equiv>>);
]
let regexp uri_step = [ 'a' - 'z' 'A' - 'Z' '0' - '9' '_' '-' ''' ]+
(* $Id$ *)
+(* FG
+ * From Cambridge dictionary
+ * Dependency:
+ * a country which is supported and governed by another country
+ * Dependence:
+ * when you need something or someone all the time, especially in order to
+ * continue existing or operating
+ *
+ * Fate vobis ...
+ *)
+
exception UnableToInclude of string
(* statements meaningful for matitadep *)
set "baseuri" "cic:/matita/RELATIONAL/NLE/defs".
+include "logic/equality.ma".
+
include "Nat/defs.ma".
inductive NLE: Nat \to Nat \to Prop \def
| NLE_zero: \forall q. NLE zero q
- | NLE_succ: \forall p,q. NLE p q \to NLE (succ p) (succ q).
+ | NLE_succ: \forall p,q. NLE p q \to NLE (succ p) (succ q)
+.
+
+(*CSC: the URI must disappear: there is a bug now *)
+interpretation "natural 'less or equal to'" 'leq x y =
+ (cic:/matita/RELATIONAL/NLE/defs/NLE.ind#xpointer(1/1) x y).
+
+(*CSC: the URI must disappear: there is a bug now *)
+interpretation "natural 'less than'" 'lt x y =
+ (cic:/matita/RELATIONAL/NLE/defs/NLE.ind#xpointer(1/1)
+ (cic:/matita/RELATIONAL/Nat/defs/Nat.ind#xpointer(1/1/2) x) y).
inductive NPlus (p:Nat): Nat \to Nat \to Prop \def
| nplus_zero_2: NPlus p zero p
| nplus_succ_2: \forall q, r. NPlus p q r \to NPlus p (succ q) (succ r).
+
+(*CSC: the URI must disappear: there is a bug now *)
+interpretation "natural plus (relational)" 'rel_plus x y z =
+ (cic:/matita/RELATIONAL/NPlus/defs/NPlus.ind#xpointer(1/1) x y z).
+
+notation "hvbox(a break + b break == c)"
+ non associative with precedence 95
+for @{ 'rel_plus $a $b $c}.
(* primitive generation lemmas proved by elimination and inversion *)
-theorem nplus_gen_zero_1: \forall q,r. NPlus zero q r \to q = r.
+theorem nplus_gen_zero_1: \forall q,r. (zero + q == r) \to q = r.
intros. elim H; clear H q r; intros;
[ reflexivity
| clear H1. auto
].
qed.
-theorem nplus_gen_succ_1: \forall p,q,r. NPlus (succ p) q r \to
- \exists s. r = (succ s) \land NPlus p q s.
+theorem nplus_gen_succ_1: \forall p,q,r. ((succ p) + q == r) \to
+ \exists s. r = (succ s) \land (p + q == s).
intros. elim H; clear H q r; intros;
[
| clear H1.
]; apply ex_intro; [| auto || auto ]. (**)
qed.
-theorem nplus_gen_zero_2: \forall p,r. NPlus p zero r \to p = r.
+theorem nplus_gen_zero_2: \forall p,r. (p + zero == r) \to p = r.
intros. inversion H; clear H; intros;
[ auto
| clear H H1.
].
qed.
-theorem nplus_gen_succ_2: \forall p,q,r. NPlus p (succ q) r \to
- \exists s. r = (succ s) \land NPlus p q s.
+theorem nplus_gen_succ_2: \forall p,q,r. (p + (succ q) == r) \to
+ \exists s. r = (succ s) \land (p + q == s).
intros. inversion H; clear H; intros;
[ lapply eq_gen_succ_zero to H as H0. apply H0
| clear H1 H3 r.
].
qed.
-theorem nplus_gen_zero_3: \forall p,q. NPlus p q zero \to p = zero \land q = zero.
+theorem nplus_gen_zero_3: \forall p,q. (p + q == zero) \to
+ p = zero \land q = zero.
intros. inversion H; clear H; intros;
[ rewrite < H1. clear H1 p.
auto
].
qed.
-theorem nplus_gen_succ_3: \forall p,q,r. NPlus p q (succ r) \to
- \exists s. p = succ s \land NPlus s q r \lor
- q = succ s \land NPlus p s r.
+theorem nplus_gen_succ_3: \forall p,q,r. (p + q == (succ r)) \to
+ \exists s. p = succ s \land (s + q == r) \lor
+ q = succ s \land (p + s == r).
intros. inversion H; clear H; intros;
[ rewrite < H1. clear H1 p
| clear H1.
(*
(* alternative proofs invoking nplus_gen_2 *)
-variant nplus_gen_zero_3_alt: \forall p,q. NPlus p q zero \to p = zero \land q = zero.
+variant nplus_gen_zero_3_alt: \forall p,q. (p + q == zero) \to
+ p = zero \land q = zero.
intros 2. elim q; clear q; intros;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0. clear H0 p.
].
qed.
-variant nplus_gen_succ_3_alt: \forall p,q,r. NPlus p q (succ r) \to
- \exists s. p = succ s \land NPlus s q r \lor
- q = succ s \land NPlus p s r.
+variant nplus_gen_succ_3_alt: \forall p,q,r. (p + q == (succ r)) \to
+ \exists s. p = succ s \land (s + q == r) \lor
+ q = succ s \land (p + s == r).
intros 2. elim q; clear q; intros;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0. clear H0 p
*)
(* other simplification lemmas *)
-theorem nplus_gen_eq_2_3: \forall p,q. NPlus p q q \to p = zero.
+theorem nplus_gen_eq_2_3: \forall p,q. (p + q == q) \to p = zero.
intros 2. elim q; clear q; intros;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0. clear H0 p
]; auto.
qed.
-theorem nplus_gen_eq_1_3: \forall p,q. NPlus p q p \to q = zero.
+theorem nplus_gen_eq_1_3: \forall p,q. (p + q == p) \to q = zero.
intros 1. elim p; clear p; intros;
[ lapply linear nplus_gen_zero_1 to H as H0.
rewrite > H0. clear H0 q
include "NPlus/fwd.ma".
-theorem nplus_zero_1: \forall q. NPlus zero q q.
+theorem nplus_zero_1: \forall q. zero + q == q.
intros. elim q; clear q; auto.
qed.
-theorem nplus_succ_1: \forall p,q,r. NPlus p q r \to NPlus (succ p) q (succ r).
+theorem nplus_succ_1: \forall p,q,r. NPlus p q r \to
+ (succ p) + q == (succ r).
intros 2. elim q; clear q;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0. clear H0 p
]; auto.
qed.
-theorem nplus_sym: \forall p,q,r. NPlus p q r \to NPlus q p r.
+theorem nplus_sym: \forall p,q,r. (p + q == r) \to q + p == r.
intros 2. elim q; clear q;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0. clear H0 p
qed.
theorem nplus_shift_succ_sx: \forall p,q,r.
- NPlus p (succ q) r \to NPlus (succ p) q r.
+ (p + (succ q) == r) \to (succ p) + q == r.
intros.
lapply linear nplus_gen_succ_2 to H as H0.
decompose.
qed.
theorem nplus_shift_succ_dx: \forall p,q,r.
- NPlus (succ p) q r \to NPlus p (succ q) r.
+ ((succ p) + q == r) \to p + (succ q) == r.
intros.
lapply linear nplus_gen_succ_1 to H as H0.
decompose.
auto.
qed.
-theorem nplus_trans_1: \forall p,q1,r1. NPlus p q1 r1 \to
- \forall q2,r2. NPlus r1 q2 r2 \to
- \exists q. NPlus q1 q2 q \land NPlus p q r2.
+theorem nplus_trans_1: \forall p,q1,r1. (p + q1 == r1) \to
+ \forall q2,r2. (r1 + q2 == r2) \to
+ \exists q. (q1 + q2 == q) \land p + q == r2.
intros 2; elim q1; clear q1; intros;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0. clear H0 p
]; apply ex_intro; [| auto || auto ]. (**)
qed.
-theorem nplus_trans_2: \forall p1,q,r1. NPlus p1 q r1 \to
- \forall p2,r2. NPlus p2 r1 r2 \to
- \exists p. NPlus p1 p2 p \land NPlus p q r2.
+theorem nplus_trans_2: \forall p1,q,r1. (p1 + q == r1) \to
+ \forall p2,r2. (p2 + r1 == r2) \to
+ \exists p. (p1 + p2 == p) \land p + q == r2.
intros 2; elim q; clear q; intros;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0. clear H0 p1
]; apply ex_intro; [| auto || auto ]. (**)
qed.
-theorem nplus_conf: \forall p,q,r1. NPlus p q r1 \to
- \forall r2. NPlus p q r2 \to r1 = r2.
+theorem nplus_conf: \forall p,q,r1. (p + q == r1) \to
+ \forall r2. (p + q == r2) \to r1 = r2.
intros 2. elim q; clear q; intros;
[ lapply linear nplus_gen_zero_2 to H as H0.
rewrite > H0 in H1. clear H0 p